Women’s Sexual Freedom in Marrital Relations - Tamta Sajaia (European Scientific Journal, ESJ, 2017)
Family relationships with its moral, social and legal nature, is a rather complex phenomenon. The circle of obligations imposed on a family is wide – it is a part of a big mechanism. The family should provide basis of morality, spirituality, tolerance which, in its turn, will guarantee the stabilization of society and minimize social problems. The family, which manifests itself in violence, especially when men violate their spouses’ sexual freedom predestined to conflict and destruction. In homes where there are similar problems, chronic irritability, stress, lack of trust and mutual respect are frequently met. Wives – victims of sexual abuse have to adapt to severe physical and mental consequences. Unfortunately, the reasons of violence very often is hidden in mental views of a particular state. In traditional countries women's obedience is a norm. Accordingly, the fear of public censure does not allow women to defend their sexual freedom and put an end to sexual abuse committed by their spouses. In many cases, wives who follow traditions and customs, consider intimate relations with their husbands as their duty, do not perceive it as violence and adapt to bullying. Overcoming the mentioned problem is even more difficult when traditional norms are deeply implemented in a particular state’s legislation and sexual relation with husbands is recognized as statutory duty. The aim of this report is to find out how the traditional society of Georgia views the recognition of women’s sexual freedom within the framework of marital relations and what normative approaches the state has.